Microbiological composition associated with vitamin D receptor gene polymorphism in chronic periodontitis - Borges,Maria Angélica Toniato (2009)
The aim of this cross-sectional study was to examine the relationship between the composition of the subgingival microbiota and the vitamin D receptor (VDR) gene polymorphism in Brazilian adults with chronic periodontitis. The clinical parameters of probing depth, clinical attachment level, bleeding on probing, plaque accumulation and suppuration were measured in 60 Caucasian adults who were divided into two groups: 30 healthy individuals (control) and 30 with chronic periodontitis (ChP). Subgingival plaque samples were collected from 6 sites per subject and analyzed for 38 bacterial species using the Checkerboard DNA-DNA Hybridization. DNA was obtained from the subjects' epithelial cells by scraping the buccal mucosa and using a mouthwash containing 3% of glucose. Polymorphism in the VDR gene was analyzed by the polymerase chain reaction (PCR), followed by Taql digestion (RFLP). The healthy subjects presented significantly lower levels (0.3 × 10(7) ± 0.7 × 10(7)) of total microbial counts in comparison with subjects with chronic periodontitis (4.5 × 10(7) ± 2.9 × 10(7)). Regarding the occurrence of VDR polymorphism, it was observed that the Tt genotype was more prevalent in the Periodontitis group (60%) than in the Healthy group (30%), while the prevalences of the TT genotype were 23.3% and 53.3%, respectively (Chi-square test, p < 0.05). No difference was found in the composition of subgingival microbiota among the VDR genotypes evaluated for the Healthy and Periodontitis groups. In conclusion, the Tt genotype was associated with periodontal disease; however, no association with the subgingival microbiota was observed.